2020
DOI: 10.1002/mus.26858
|View full text |Cite
|
Sign up to set email alerts
|

Quality of electrodiagnostic testing for carpal tunnel syndrome: adherence to quality measures

Abstract: Introduction Research has shown that quality of health‐care services is often suboptimal. Little is known about the quality of electrodiagnostic testing. Methods We prospectively recruited 477 adults with workers' compensation claims for carpal tunnel syndrome (CTS) from 30 occupational health clinics and evaluated whether electrodiagnostic testing adhered to five process‐oriented quality measures. Results Among patients who had surgery for CTS, nearly all underwent recommended preoperative electrodiagnostic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Process‐oriented measures are tools for evaluating whether care adheres to recommended standards 12,13 . As described in an accompanying study, we found that, in a prospectively recruited population with workers’ compensation claims for CTS, electrodiagnostic test quality was variable 14 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Process‐oriented measures are tools for evaluating whether care adheres to recommended standards 12,13 . As described in an accompanying study, we found that, in a prospectively recruited population with workers’ compensation claims for CTS, electrodiagnostic test quality was variable 14 …”
Section: Introductionmentioning
confidence: 99%
“…12,13 As described in an accompanying study, we found that, in a prospectively recruited population with workers' compensation claims for CTS, electrodiagnostic test quality was variable. 14 Based on the same study population and four quality measures that address how electrodiagnostic tests are performed and interpreted, the present analysis had two objectives. First, we sought to quantify the degree to which accounting for test quality alters the appropriateness (ie, risk-benefit ratio) of surgery for CTS.…”
mentioning
confidence: 99%
“…The issues of what constitutes the essential components of a high‐quality EDx examination may be considered from many perspectives. We agree with the criteria used by Aragaki et al, 1 but we also recognize this is not without some controversy. Whichever criteria are adopted, the skill with which these are executed should be of concern as well.…”
mentioning
confidence: 99%
“…In this issue of the Journal, Aragaki et al 1 Practice parameters have been published addressing both CTS diagnosis and treatment. [3][4][5][6][7][8] Despite these specific guidelines, several studies have demonstrated that only a minority of clinicians perform high-quality EDx studies for the evaluation of CTS.…”
mentioning
confidence: 99%
See 1 more Smart Citation